'SWEATCH': A Wearable Platform for Harvesting and Analysing Sweat Sodium Content. Issue 6 (27th April 2016) - Glennon, Tom; O'Quigley, Conor; McCaul, Margaret; Matzeu, Giusy; Beirne, Stephen; Wallace, Gordon G.; Stroiescu, Florin; O'Mahoney, Niamh; White, Paddy; Diamond, Dermot
Abstract: A platform for harvesting and analysing the sodium content of sweat in real time is presented. One is a 'watch' format in which the sampling and fluidic system, electrodes, circuitry and battery are arranged vertically, while in the other 'pod' format, the electronics and battery components, and the fluidics electrodes are arranged horizontally. The platforms are designed to be securely attached to the skin using a velcro strap. Sweat enters into the device through a sampling orifice and passes over solid‐state sodium‐selective and reference electrodes and into a storage area containing a high capacity adsorbent material. The liquid movement is entirely driven by capillary action, and the flow rate through the device can be mediated through variation of the width of a fluidic channel linking the electrodes to the sample storage area. Changing the width dimension through 750, 500 and 250 µm produces flow rates of 38.20, 21.48 and 6.61 µL/min, respectively. Variation of the sweat uptake rate and the storage volume capacity enables the duration of usage to be varied according to the needs of the user. The devices can be easily disassembled to replace the electrodes and the high capacity adsorbant material. The storage sweat is available for subsequent measurement of the total volume of sweat harvested and the average concentration of sodium over the period of use. Signals generated by the electrodes are passed to a custom designed electronics board with high input impedance to accurately capture the voltage. The real‐time data is transmitted wirelessly using incorporated Bluetooth circuitry to a remote basestation (laptop, mobile phone, tablet) for data visualization and storage in standard formats. Results obtained during trials over a period of ca. 30 minutes controlled exercise are consistent with previously published data, showing a gradual relatively slow increase of the sodium concentration in the sweat during this period. Abstract :